2020
DOI: 10.1038/s41598-020-78674-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal denervation normalizes aortic function and decreases blood pressure in spontaneously hypertensive rats

Abstract: Mechanisms involved in the acute responses to renal denervation (RDN) have yet to be fully understood. We assessed urinary volume, autonomic control and aorta vascular reactivity after acute RDN. Male normotensive Wistar rats and spontaneously hypertensive rats (SHR) were divided into normotensive + RDN (ND) or sham surgery (NS), and hypertensive + RDN (HD) or sham surgery (HS). Metabolic parameters and hemodynamic measurements were recorded 72h and 4 days after intervention, respectively. Aortic rings were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…Selective afferent renal denervation has no effect on baseline BP in these rats, thus, renal efferents control baseline BP (Banek et al, 2016; Foss et al, 2015; Jacob et al, 2003; Osborn & Foss, 2017). However, other studies denervated the same rat strain and found no baseline BP alterations, which is compatible to findings from other rat strains and mice (Asirvatham‐Jeyaraj et al, 2016; Foss et al, 2018; Gueguen et al, 2019; Hohl et al, 2022; Moreira et al, 2020; Xiao et al, 2015). Further studies have to be performed to test if the species and/or background strain or rather technical issues like denervation efficacy are decisive.…”
Section: Discussionsupporting
confidence: 87%
“…Selective afferent renal denervation has no effect on baseline BP in these rats, thus, renal efferents control baseline BP (Banek et al, 2016; Foss et al, 2015; Jacob et al, 2003; Osborn & Foss, 2017). However, other studies denervated the same rat strain and found no baseline BP alterations, which is compatible to findings from other rat strains and mice (Asirvatham‐Jeyaraj et al, 2016; Foss et al, 2018; Gueguen et al, 2019; Hohl et al, 2022; Moreira et al, 2020; Xiao et al, 2015). Further studies have to be performed to test if the species and/or background strain or rather technical issues like denervation efficacy are decisive.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, WKY rats had earlier reductions in cardiac function when compared with Wistar rats. Due to these factors, some authors have actually used or suggested the use of Wistar rats as a control for SHR in several conditions [ 31 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that renal denervation does not significantly alter arterial pressure in spontaneously hypertensive rats (SHR) over a short period of 1 h, despite interfering with intrarenal function (such as increasing RBF, dynamic autoregulation of RBF, and variability of RBF). [ 74 ] Meanwhile, despite causing systemic hypotension, RSDN does not affect perfusion and renal function at various intervals (directly and after 3 months) and does not alter RBF in patients with hypertension. [ 75 ] Hence, it can be deduced that the effect of RSDN is negligible on acute or chronic renal perfusion.…”
Section: Renal Sympathetic Denervation and Renal Blood Flowmentioning
confidence: 99%